Influence of parametric uncertainties on the deflection statistics of general laminated composite and sandwich plates. (1st July 2017) - Grover, Neeraj; Sahoo, Rosalin; Singh, B.N.; Maiti, D.K.
Abstract: The influence of parametric uncertainties on the deflection statistics of laminated composite and sandwich plates is examined in the present work. The laminated composite and sandwich plates are modeled in an axiomatic framework employing inverse hyperbolic shear deformation theory. The parametric uncertainties particularly to material properties are modeled using first order perturbation technique (FOPT). A robust stochastic finite element analysis solver based on FOPT is developed and employed to examine the second order deflection statistics of laminated composite and sandwich plates. The validity of the developed stochastic finite element solver is ensured by comparing the present deflection statistics to that of independently developed Monte Carlo Simulation based on the deterministic finite element solver. Also, the results are compared with the existing results and the applicability and validity of present technique is ensured. It is concluded that the uncertainties associated with the material properties have influence on the bending response of laminated composite and sandwich plates. However, the extent of this influence depends on the geometric parameters, boundary constraints, loading parameters and lamination sequence. The influence of material uncertainties under such conditions is examined quantitatively and indicative conclusions are observed.